1992
DOI: 10.1002/polb.1992.090301103
|View full text |Cite
|
Sign up to set email alerts
|

Free volume in glassy poly(arylene ether ketone)s

Abstract: Amorphous polyarylene ether ketones were examined in the glassy state by positron annihilation lifetime spectroscopy (PALS) and in the melt by standard rheological techniques. Specimens were well‐characterized fractions of two isomeric structures. PALS clearly shows that the polymer with meta linkages in its backbone contains larger voids (> 0.25 nm radius). Thus despite their similar bulk densities, the two materials must pack very differently on a local scale. On the other hand, the free volumes inferred fro… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
9
0

Year Published

1994
1994
2009
2009

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 12 publications
(9 citation statements)
references
References 11 publications
0
9
0
Order By: Relevance
“…The functional forms of Equations (18) and (19) clearly assign higher probabilities to microstates with lower energies. Results Tables 1 and 2 show the results obtained from the MD simulations of each microstate of the polyimide and polycarbonate materials, respectively.…”
Section: Energy-based Statisticsmentioning
confidence: 95%
See 2 more Smart Citations
“…The functional forms of Equations (18) and (19) clearly assign higher probabilities to microstates with lower energies. Results Tables 1 and 2 show the results obtained from the MD simulations of each microstate of the polyimide and polycarbonate materials, respectively.…”
Section: Energy-based Statisticsmentioning
confidence: 95%
“…The probability distributions described by Equations (18) and (19) obey the normalization condition of Equation (17). The functional forms of Equations (18) and (19) clearly assign higher probabilities to microstates with lower energies.…”
Section: Energy-based Statisticsmentioning
confidence: 99%
See 1 more Smart Citation
“…The finite-chain network can only sample a small portion of the conformational space of the bulk polymer. As a result, the physical properties of a polymer can vary substantially on the nanometer length-scale [14][15][16][17][18][19][20][21][22][23]. Similarly, the RVE size can influence the predicted mechanical properties of a polymer [24] using multiscale modeling techniques.…”
Section: Introductionmentioning
confidence: 99%
“…10 Over the last two decades, to accommodate the enormous applications, the crystallization and melting behavior have been studied extensively via differential scanning calorimetry (DSC), [11][12][13][14][15][16] smallangle X-ray scattering (SAXS) and wide-angle X-ray diffraction (WAXD), [17][18][19][20][21][22][23][24] thermomechanical analysis, [25][26][27] transmission electron microscopy (TEM), 28,29 and optical microscopy (OM). [20][21][22][23][24][25][26][27][28][29][30][31][32][33] The process of bulk crystallization of PEEK was studied through the separation of the nucleation and growth steps by Medellin-rodriguez and Phillips. 34 It was observed that a first slope at low crystallization times is associated with massive heterogeneous nucleation and/ or local-order-promoted primary nucleation of spherulitic crystal.…”
Section: Introductionmentioning
confidence: 99%